Avaliação do desempenho de uma unidade em escala real para tratamento de água pluvial empregando a filtração direta por meio de filtro de pressão e amido natural de milho como coagulante primário - Murakami, Marcela Ferreira; Moruzzi, Rodrigo Braga [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2013)
The aim of this study was to investigate the performance of an experimental rainwater treatment system for non-potable uses. Without the first-flush discharge it was expected to control the quality of captured rainwater and to minimize the rainwater by-pass caused by the first-flush strategy. A full-scale direct filtration unit was operated and a solution of natural corn starch was used as the primary coagulant. The color, turbidity e coliform efficiencies of the unit was analyzed based on filtration loads and the net water production was estimated. The results pointed out turbidity removal up to 70.8% and color removal up to 61.0%. The backwash of the filtering system was completed in 3 minutes at the rate of 1,440 m3/m2day with consumption of treated water from 0.5% to 2.2%, based on the potentially harvesting.
Performance analyses of a full-scale rainwater treatment unit using direct filtration and starch as primary coagulant
Keywords: Catchment; Economy; Rainwater; Treatment; Utilization